Oxidative Stress, NF-κB-Mediated Inflammation and Apoptosis in the Testes of Streptozotocin-Induced Diabetic Rats: Combined Protective Effects of Malaysian Propolis and Metformin - Victor Udo Nna; Ainul Bahiyah Abu Bakar; Azlina Ahmad; Chinedum Ogbonnaya Eleazu; Mahaneem Mohamed (MDPI AG, 2019)
Oxidative stress, inflammation and apoptosis are major complications that trigger organ failure in diabetes mellitus (DM), and are proven to adversely affect the male reproductive system. Clinical and experimental studies have demonstrated the promising protective effects of propolis in DM and its associated systemic effects. Herein, we investigated the effect of Malaysian propolis (MP) on testicular oxidative stress, inflammation and apoptosis in diabetic rats. Further, the possibility of a complementary effect of MP with the anti-hyperglycaemic agent, metformin (Met), was studied with the idea of recommending its use in the event that Met alone is unable to contain the negative effects of DM on the male reproductive system in mind. Male Sprague-Dawley rats were either gavaged distilled water (normoglycaemic control and diabetic control groups), MP (diabetic rats on MP), Met (diabetic rats on Met) or MP+Met (diabetic rats on MP+Met), for 4 weeks. MP decreased oxidative stress by up-regulating (p < 0.05) testicular mRNA levels of nuclear factor erythroid 2-related factor 2, superoxide dismutase, catalase and glutathione peroxidase; increasing (p < 0.05) the activities of antioxidant enzymes; and decreasing (p < 0.05) lipid peroxidation in the testes and epididymis of diabetic rats. Further, MP down-regulated (p < 0.05) testicular mRNA and protein levels of pro-inflammatory mediators (nuclear factor kappa B, inducible nitric oxide synthase, tumour necrosis factor-α and interleukin (IL)-1β), decreased (p < 0.05) the nitric oxide level, and increased (p < 0.05) IL-10 mRNA and protein levels. MP also down-regulated (p < 0.05) Bax/Bcl-2, p53, casapase-8, caspase-9 and caspase-3 genes, and increased (p < 0.05) testicular germ cell proliferation. MP’s effects were comparable to Met. However, the best results were achieved following co-administration of MP and Met. Therefore, we concluded that administration of the MP+Met combination better attenuates testicular oxidative stress, inflammation and apoptosis in DM, relative to MP or Met monotherapy, and may improve the fertility of males with DM.